2021
DOI: 10.1177/15266028211030527
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Clinical Outcome and Risk Factor Analysis of Directional Atherectomy Followed With Drug-Coated Balloon for Femoropopliteal Artery Disease

Abstract: Purpose: This study investigated the 1-year clinical outcomes of directional atherectomy combined with drug-coated balloon (DA + DCB) in femoropopliteal artery disease (FPAD) from real-world experience. Materials and Methods: A retrospective study was conducted of patients treated between July 2016 and June 2019 using DA + DCB for FPAD. Patients’ demographics, comorbidities, clinical characteristics and outcomes, and angiography and duplex ultrasound findings were analyzed. The 6-month and 1-year primary paten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…Although these anatomical features have a major impact on loss of primary patency after EVT, 11–15 the 12‐month primary patency in this trial was comparable to that of approved DCBs, demonstrating that the novel technical design and characteristics of the TCD‐17187 DCB ensured a good balance between drug retention during balloon delivery to the lesion and effective drug transit to the vessel wall to optimize drug uptake, achieving durable results without any increased risk of adverse events including the downstream effect adjudicated by core laboratory. Univariate analysis of variables for loss of primary patency revealed that presence of CTO was the sole anatomical factor for loss of patency with an HR of 2.39, which was consistent with the results obtained in other DCB studies, 16,17 while other clinical and lesion factors including vessel diameter, lesion length, and severity of vessel calcification were not statistically significant. These results potentially represent an insight into the specific features of the TCD‐17187 DCB, but the sample size of this trial was limited and these findings need to be confirmed in real‐world practice.…”
Section: Discussionsupporting
confidence: 88%
“…Although these anatomical features have a major impact on loss of primary patency after EVT, 11–15 the 12‐month primary patency in this trial was comparable to that of approved DCBs, demonstrating that the novel technical design and characteristics of the TCD‐17187 DCB ensured a good balance between drug retention during balloon delivery to the lesion and effective drug transit to the vessel wall to optimize drug uptake, achieving durable results without any increased risk of adverse events including the downstream effect adjudicated by core laboratory. Univariate analysis of variables for loss of primary patency revealed that presence of CTO was the sole anatomical factor for loss of patency with an HR of 2.39, which was consistent with the results obtained in other DCB studies, 16,17 while other clinical and lesion factors including vessel diameter, lesion length, and severity of vessel calcification were not statistically significant. These results potentially represent an insight into the specific features of the TCD‐17187 DCB, but the sample size of this trial was limited and these findings need to be confirmed in real‐world practice.…”
Section: Discussionsupporting
confidence: 88%
“…There is a focus on more complex and combined techniques for the treatment of ISRs which are producing more encouraging results such as DES, again with major limitations such as a stent length which excludes treating long stenosis. DCB shows superior results compared to traditional re-PTA with a stent and is becoming the technique of choice for ISRs [ 12 , 13 , 14 , 15 , 62 ]. Combined techniques such as laser atherectomy and DCB are also being developed and appear to be candidates to become the reference technique, but adequate studies are warranted [ 1 , 11 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to all the data collected on the efficacy of the specific drug, the anatomy of the stenosis should also be carefully considered. Feng et al [ 14 ] specifically evaluated the length of the stenosis by dividing the patients into two main categories. CTO (chronic total occlusion) >10 cm, in the reported analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations